Analysis of the double regulation of electrical installations, based on industrial safety and electrical risk (AACINI - International Journal of Industrial Engineering, 2023)
The electrical utilities are an important source of danger in buildings, so it is necessary that they be designed, executed and used with very strict criteria, these criteria must guarantee the safety of people and things in their vicinity.In Spain, the safety of electrical installations is regulated from two areas, such as the industrial safety regulations (Industry Law 21/1992, Low Voltage Electrotechnical Regulation, High Voltage Line Regulation...) and the regulations of occupational risk prevention ( Law 31/1995 on Occupational Risk Prevention and Royal Decree 614/2001 on electrical risk prevention). In this paper we carry out a comparative analysis of these two regulations; most of these concepts are common, they are complementary regulations but at the same time some divergences appear, particularly in terms of the levels of training required. The main conclusion reached by this paper is that in order to achieve professional excellence it is essential to comply with both regulations, and that any person exposed to electrical risk knows both regulations.
Keywords: electrical risk; electrotechnical regulations; occupational risk prevention; high voltage and low voltage